Socio-Cultural Values and Ecological Awareness in Sakela Sili in Kirant Rai in Nepal - Rai, Prakash (Literary Studies, 2021)
In the Eastern part of Nepal, Kirant Rai in traditional attires perform Sakela Sili, a dance style performed twice a yearin a larger circle to honour of Sakela, a deity in Kirant Rai community. The performance of Sakela or Sakkew involves singing and dancing simultaneously. Sakela connects the Kirant to their original source of energy, cultural root, origin and the civilization. Ethnic Kirant Rai, including youth and the old in their dance steps of working in the farmland and worshiping gods, with their hands and legs raising low and high, embody their connections to the terrestrial and celestial, profane and sacred, and the humanity and the divinity to maintain a perfect balance of art and life. The dancers in their body movements blend their passionate intensity to work and aesthetic response to art and embody socio -cultural practices and ecological awareness. While dancing, they work and dance for representing the life in totality. The Kirant Rai work pleasingly, and they dance with their strong passion to work. This paper as an instance of qualitative research employs both emic and etic perspectives to find out how such Sakela Sili performed shapes the socio - cultural values and ecological awareness among Kirant Rai community.